Disruptive 3D printing - Anderhofstadt, Ralf; Disselkamp, Marcus (Hanser, 2023)
Unites the two sides of additive manufacturing: 1) the technical aspect of 3D printing and 2) the disruptive consequences for value chains between producers, intermediaries, and customers due to modern business models. This book both shows the dangers of disruptive 3D printing technology, and offers solution approaches and procedural models.
Keywords: Three-dimensional printing.; elektronické knihy; electronic books